Desarrollo de una aplicación multiplataforma para agendamiento de citas del consultorio odontológico nz dental de cañar utilizando la metodología Design Sprint - Parra Andrade, Jairo Fernando (2023)
The objective of this study is to analyze the methodology of Design Sprint, it is focused on the creation of prototypes of a web and mobile application (multiplatform) to make schedules in the dental office NZ Dental at the city of Cañar. For the development of the multiplatform application that allows the user to create schedules directly from their home, this methodology was used. The methodology allows for classifying and validating ideas, understanding, and analyzing the problem, designing ideas, proposing solutions, and thus improving the quality of the product. The time and resources used for the generation of the project are reduced. In turn, through the analysis of the ISO/IEC 25010 standard, made up of eight general quality characteristics, the performance efficiency characteristic was further evaluated. The performance efficiency characteristic was subdivided into three sub-characteristics, defined as temporal behavior, response time and resource utilization, RAM, and memory Storage. For the performance tests of the mobile application, different simulations were carried out. Utilizing the Apache JMeter tool, real-time requests were made, and varied benchmark applications were used, for both Android and iOS devices. The results obtained from the simulations carried out in Apache JMeter demonstrated that the multiplatform application (Android and IOS) performed most adequately in relation to the proposed results, in that way, it was optimal in the two operating systems, based on the metrics proposed for the study.